What Types of Personalisation Are Used in Pregnancy Apps: A Scoping Review - FARIČ, NUŠA (Anali PAZU HD, 2024)
Digital support is a preferred source of information for pregnant women with personalisation being a key selling benefit for pregnancy apps. Pregnancy apps are the most popular type of health app (n= 2,900). To describe the variety and use of personalisation in pregnancy apps. A scoping review was performed using OvidSP databases using MEDLINE, EMBASE, PsychINFO to identify relevant articles up until August 2017. 1,121 articles were identified after excluding duplicates. Six studies met inclusion criteria (one interview study, one online survey, two app reviews; two studies using critical discourse analysis). Different dimensions of personalisation were described based on Blom’s (2000) definition of personalisation. Personalisation in pregnancy apps is largely determined by the functionality of the app (type of pregnancy app). There are no pregnancy apps that use all of the dimensions of personalisation described in this review. Future research should focus on personalising apps to reach underrepresented populations.
Keywords: women's health; pregnancy; smartphone; review; mHealth